2020
DOI: 10.14444/7061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium Miniplate Fixation on Hinge Fracture and Hinge Fracture Displacement Following Cervical Open-Door Laminoplasty

Abstract: Background: Cervical spondylotic myelopathy is a neuromotor disorder responsible for functional limitations and decreased daily activities. Expansive open-door laminoplasty is the widely accepted procedure for the treatment of multilevel cervical spondylotic myelopathy. Among the various fixation procedures to secure the open lamina, miniplate fixation provides better clinical and radiological outcomes. However, the immediate effects on hinge fracture and hinge fracture displacement following miniplate fixatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…In many long-term follow-up studies over the past 2 decades, open-door laminoplasty has been proven to be an effective and simple surgical procedure for the treatment of multilevel CSM [ 2 4 , 6 8 ]. With the continuous development and innovation of surgical internal fixation devices, the fixation method of lamina has also changed from the initial suture suspensory to an anchor, and mini-titanium plates are widely used at this stage [ 3 , 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In many long-term follow-up studies over the past 2 decades, open-door laminoplasty has been proven to be an effective and simple surgical procedure for the treatment of multilevel CSM [ 2 4 , 6 8 ]. With the continuous development and innovation of surgical internal fixation devices, the fixation method of lamina has also changed from the initial suture suspensory to an anchor, and mini-titanium plates are widely used at this stage [ 3 , 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous development and innovation of surgical internal fixation devices, the fixation method of lamina has also changed from the initial suture suspensory to an anchor, and mini-titanium plates are widely used at this stage [ 3 , 4 , 9 ]. Through a clinical meta-analysis, Mo et al [ 8 ] found that compared with suture suspensory and anchor fastening, mini-titanium plate fixation can reduce the loss of range of motion, and the incidence of axial symptoms and C5 palsy is reduced. To maintain the opening state of the lamina, the silk thread can be sutured to the opposite articular capsule, and the anchor can be placed at the midpoint of the lateral mass on the hinge side.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations